(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Motivation plays a pivotal role in the success of learners in English as a Foreign Language (EFL) contexts. This paper explores the most effective motivational strategies employed by teachers to foster student engagement and language proficiency. Drawing on current research and classroom practices, the study examines both intrinsic and extrinsic motivators, classroom climate, teacher-student interaction, and the role of learner autonomy. Results highlight that diversified strategies aligned with students’ needs significantly enhance language learning outcomes.